Principals' Struggle To Level the Accountability Playing Field of Florida Graded "D" and"F" Schools in High Poverty and Minority Communities - Acker-Hocevar, Michele; Touchton, Debra ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
This study examined the perceptions of Florida principals from failing high poverty/minority schools regarding accountability measures placed upon their schools by state legislation. Data collection included field notes, observations, and interviews regarding principals' impressions of the state's accountability system, how their role was influenced by the system, and how they negotiated internal and external accountability. Four themes emerged: effects of poverty on teaching and learning, building organizational capacity, high stakes testing, and recruitment and retention of teachers. Principals felt they faced continual pressure to improve student performance and meet state and district mandates while supporting teachers and students. They believed their everyday problems were very different from those of peers in less diverse schools. Principals were not against Florida's standards or accountability but rather the inequity of using high stakes testing to compare students with different needs when grading schools. They believed they needed more time to raise student achievement levels. They recognized that their schools concentrated on short-term change due to the urgency of improving their failing grades. Principals felt threatened by mandates from the top. They reported losing teachers to other professions and schools because of poor teaching conditions. They fought districts for more teachers to reduce class size. (Contains 26 references.) (SM)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (Seattle, WA, April 10-14, 2001).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Accountability; Administrator Attitudes; Administrator Role; Educational Improvement; Elementary Secondary Education; Equal Education; High Stakes Tests; Leadership; Minority Group Children; Poverty; Principals; School Effectiveness; State Legislation; State Standards; Teacher Persistence; Teacher Recruitment; Florida; Reports, Research; Speeches/Meeting Papers